2016
DOI: 10.1186/s13063-016-1498-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a new technique – INtubate-RECruit-SURfactant-Extubate – “IN-REC-SUR-E” – in preterm neonates with respiratory distress syndrome: study protocol for a randomized controlled trial

Abstract: BackgroundAlthough beneficial in clinical practice, the INtubate-SURfactant-Extubate (IN-SUR-E) method is not successful in all preterm neonates with respiratory distress syndrome, with a reported failure rate ranging from 19 to 69 %. One of the possible mechanisms responsible for the unsuccessful IN-SUR-E method, requiring subsequent re-intubation and mechanical ventilation, is the inability of the preterm lung to achieve and maintain an “optimal” functional residual capacity. The importance of lung recruitme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…The intervention will be regarded as being successful if it lowers the rate of the primary endpoints to 30%. This follows the expectations within similar studies [15]. To lower the rate of primary endpoints from 50 to 30% and to confirm this via Cochran-Mantel-Haenszel test (level of significance = 0.05, power = 80%), a sample size of 103 patients per group will be needed.…”
Section: Sample Size {14}supporting
confidence: 73%
“…The intervention will be regarded as being successful if it lowers the rate of the primary endpoints to 30%. This follows the expectations within similar studies [15]. To lower the rate of primary endpoints from 50 to 30% and to confirm this via Cochran-Mantel-Haenszel test (level of significance = 0.05, power = 80%), a sample size of 103 patients per group will be needed.…”
Section: Sample Size {14}supporting
confidence: 73%
“…However, the INSURE (intubation-surfactant-extubation) technique of surfactant administration is an invasive operation, and it is not successful in all preterm neonates with RDS, with a reported failure rate ranging from 19 to 69%. And the unsuccessful INSURE technique required subsequent intratracheal ventilation [18]. In our review with meta-analysis from two trials of Li et al [10] and Colnaghi et al [12], a remarkable decrease was demonstrated for the need of surfactant in the group of infants who received Heliox, and the difference was statistically significant.…”
Section: Discussionmentioning
confidence: 84%
“…In this retrospective study of very low birth weight infants, they showed that positive pressure ventilation (PPV) use in DR using RAM NC resulted in less need for intubation, chest compressions, and epinephrine administration when compared with a face mask for PPV in the DR. 8 Other pulmonary recruitment strategies in the DR, such as the use of sustained inflation (SI) and caffeine in the DR, are currently being evaluated. 9,10 Since November 2016, as part of an ongoing trial named IN-REC-SUR-E (INtubate-RECruit-SURfactant-Extubate), 11 our group has standardized the approach to extremely low GA neonates (ELGANs) in the DR with the use of a protocol that includes SI 9 followed by a nasal continuous positive airway pressure (NCPAP) (range: 6-8 cm of H 2 O) delivered through RAM NC. Prior to this time period, these infants were resuscitated with SI using face mask followed by the application of CPAP of 5 cm H 2 O with a nasopharyngeal tube.…”
mentioning
confidence: 99%